Oral Condition of Three Yanomama Indian Tribes of South America - Cléber Bidegain Periera; Joseph P. Katich; Christy G. Turner II (Dental Anthropology Association, 1994)
The permanent dentition and supporting tissue of 140 Yanomama Indians ranging in age from three to more than 40 years was examined for malocclusion, caries, attrition, and periodontal disease. Their oral status is characterized by malocclusion (79%), anterior tooth crowding (55%), a low frequency of caries (14%), periodontal disease (83%), and a linear progression of occlusal attrition with age. The Yanomama are recognized as having been geographically, genetically, and linguistically isolated for a minimum of 500 years. This situation permits the use of their dental condition to assess the hypotheses that admixture and/or tooth use is chiefly responsible for the widespread malocclusion found in many modern Yanomama populations. Because the Yanomama have seemingly not been affected by foreign admixture, and because they possess marked tooth wear evidencing heavy mastication, neither admixture nor lack of masticatory function can be responsible for a high degree of malocclusion.